A Survey Study on Indian IT Firms Attitude towards Foreign Exchange Exposure Management - R. H., Raghavendra; P. S., Velmurugan (Gyan Management Journal, 2015)
In the light of globalization and internationalization of world markets, foreign exchange risk has  become one of the most difficult and persistent problems with which financial executives must cope.  This risk cannot be avoided, but can be managed by hedging instruments. The need and approach for  managing it depends on the size of exposure and fluctuations in exchange rate. Indian IT sector is  known for development of software and it mainly depends on exports. They are required to measure  and manage exchange rate risk. The survey study on IT firma attitude towards foreign exchange  exposure management is virtually non-existent. Hence, an attempt is made in this paper to fill this gap,  by documenting the Indian IT firms attitude towards forex exposure management practice.
Keywords: Currency hedging; attitude; concerns; perceptions and exchange risk